Coenzyme, cofactor and prosthetic group : ambiguous biochemical jargon - Hashim, Onn Haji; Adnan, N.A. (1994)
For enzymes which require non-protein components to be functionally active, it is generally accepted that the term holoenzyme refers to the complete catalytic entity which consists of a protein part known as the apoenzyme and a non-protein constituent. The terms used for the functionally required non-protein constituents however, are ambiguous and differ from one commonly used biochemistry textbook to another. In certain textbooks, any associative non-protein factor required for the enzymatic function is termed coenzyme. The coenzyme may eitherbe a prosthetic group — the tightly bound coenzyme, or a cofactor — the loosely bound small organic or inorganic molecule.